2019
DOI: 10.1177/1744629519886184
|View full text |Cite
|
Sign up to set email alerts
|

Medication management in intellectual disability settings: A systematic review

Abstract: There is a high level of medication usage among people with intellectual disability due to the presence of significant morbidity and co-morbidities. This review sought to explore medication management and administration in intellectual disability settings, identifying frameworks for practice, analysing whether collaborative practice led to better outcomes, identifying key processes associated with practice, locating tools to support practice and describing metrics for outcome measurement. A systematic review w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…The innovation in this study is that we included all three conditions, intellectual and developmental disabilities, HTN, and MI, and examined whether adherence to psychotropic medication is a mediator in the pathway of residency type and antihypertensive medication adherence. Furthermore, a recent systematic review on the management of medication in intellectual disability settings found a lack of information on management, adherence, or compliance of medications (Sheerin et al, 2019). Of the 64 studies, two were related to the adherence of medication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The innovation in this study is that we included all three conditions, intellectual and developmental disabilities, HTN, and MI, and examined whether adherence to psychotropic medication is a mediator in the pathway of residency type and antihypertensive medication adherence. Furthermore, a recent systematic review on the management of medication in intellectual disability settings found a lack of information on management, adherence, or compliance of medications (Sheerin et al, 2019). Of the 64 studies, two were related to the adherence of medication.…”
Section: Discussionmentioning
confidence: 99%
“…Adults with intellectual and developmental disabilities have 2–3 times higher rates of psychiatric disorders and higher rates of HTN compared to the general population (Ahrnsbrak et al, 2017; Buckles et al, 2013; Stevens et al, 2014); thus, individuals with a dual-diagnosis of intellectual and developmental disabilities and a psychiatric disorder are an important subgroup to target to improve medication adherence. Despite the knowledge that there are challenges for psychiatric and hypertension medication adherence, there are insufficient programs designed for the large group of home and community-based caregivers, outside of structured group homes and supervised apartments, about these issues (Sheerin et al, 2019; Tan et al, 2015). State disability agencies provide services such as case management and community support, including job coaching, day programs, and respite to families (Petner-Arrey and Copeland, 2015); however, there is little evidence that education and information is routinely provided to families.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relevant search terms (keywords) and controlled vocabulary related to the core concepts of the research question were developed with reference to relevant literature [ 43 , 44 ]. The core concepts were (1) people with ID, (2) medication adverse effects and (3) measures or specific rating scales.…”
Section: Methodsmentioning
confidence: 99%
“…3,4 Specifically, people living with intellectual disability appear to endure unique barriers to safe medicine use across the entire medicine pathway from prescribing, dispensing, administration and adherence, and monitoring, resulting in their experience of relatively high rates of preventable adverse medication incidents. [5][6][7][8][9][10][11] To this end, the Commission recognises a requirement for the development of practical refinements to the application of all of its mainstream standards, called 'reasonable adjustments', to optimise the quality and safety of healthcare delivery for people living with intellectual disability. 12,13 Within health settings, reasonable adjustments have been interpreted to mean refinements to usual clinical processes and organisation intended to reduce barriers and improve access to, and participation of, people living with disabilities in healthcare.…”
mentioning
confidence: 99%